In the aisles [videorecording (DVD)] - Stuber, Thomas, 1981-; Stuber, Thomas, 1981-; Hüller, Sandra; Rogowski, Franz; Kurth, Peter, 1957-; Meyer, Clemens, 1977- (Music Box Films, 2019)
When a shy, lonely young man loses his job and starts working at a big box store, he falls in love with a married co-worker.